The Effect of Public Debt on Energy-Growth Nexus: Threshold Regression Analysis - Sze, Wei Yong; Hooi, Hooi Lean; Kueh, Jerome (Universiti Sains Malaysia, 2016)
ASEAN countries are dealing with challenging external environment recently with the deterioration of the global commodity price and the volatility of oil price. Most of the developing countries rely heavily on the energy consumption for the economic development purpose especially ASEAN countries which are the major energy exporter like Malaysia and Indonesia. This study aims to examine the relationship between energy consumption and economic growth from the perspective of public debt for Indonesia and Malaysia between periods of 2000 - 2013 via the threshold regression analysis. Our empirical results indicate that there are significant relationship between energy consumption and economic growth from the public debt threshold perspective for both countries. The analysis of Indonesia shows that higher level of public debt will lead to greater impact on energy consumption and economic nexus. In contrast, the impact of the energy consumption on economic growth for the case of Malaysia indicates a diminishing trend in the energy and economic growth nexus when the public debt is above the threshold level. Important policy implication from this study suggests that Indonesia and Malaysia should be more careful in formulating the energy consumption related policy by considering different perspectives such as public debt level of the nation. Moreover, both countries should consider reducing their dependence on the nonrenewable energy resources and shifting to renewable energy resources such as solar, hydro, landfill gas for their economic development in the future.